MATERI DAKWAH DALAM TAFSIR SURAH DHUHA - Tabsyir Masykar (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2018)
The most important form of da'wah is calling people to the right path blessed by Allah. Therefore, it is important to develop da'wah content derived from the Quran such as from the verses in the Surah Ad-Dhuha. The surah is the Meccan surah, revealed to the Prophet in Mecca. Based on its content, interpretation, and revelation motives, it is apparent that the Surah conveys da'wah content such as aqeeda, sharia and akhalaq. Every verse in the Surah has been relevant for quote in facing the past and current social dynamic of Muslim and non-Muslim societies.